Candi Bumi Ayu Sebagai Sumber Belajar Kontekstual Dalam Pembelajaran Sejarah - Akbar, Aziz; Syarifuddin, Syarifuddin; Pamulaan, Alif Bahtiar (FLORESIENSIS, 2024)
The Bumi Ayu Temple is a historical relic that is rich in cultural and educational values, a relic that originated from the Srivijaya Empire. Bumi Ayu Temple is synonymous with statues and reliefs that are rich in historical and cultural values of the Srivijaya Empire. This article aims to explore the potential of Bumi Ayu Temple as a contextual learning resource in history learning. The method used is a literature study that identifies various historical and cultural aspects contained in the temple. The results show that Bumi Ayu Temple can be used as an effective learning media, because it not only presents historical information, but also to understand the social and cultural context of the past. With a contextual approach, history learning is expected to be more interestingly relevant, increasing their interest and understanding of cultural heritage.